NYERI PUNGGUNG BAWAH: PENYEBAB DAN CARA PENCEGAHANNYA - Chondro, Fransisca; Sudarma, Verawati; Chudri, Juni; Handayani, Astri; Adhari, Nazwa Nathania; Putri, Rahma Arifa; Sipayung, Putra Raja Imanuel; Suryaningtyas, Maheswari Adhiatie Moerti (Jurnal Pengabdian Masyarakat Trimedika, 2026)
Low Back Pain (LBP) is a musculoskeletal health problem that is a leading cause of disability and reduced quality of life, particularly among adults engaged in physically demanding activities, non-ergonomic working postures, and repetitive domestic tasks. Nagrak Village, Bogor Regency, is predominantly inhabited by adults, especially women who work as housewives and informal physical workers, placing them at high risk of developing LBP. Limited community knowledge regarding the causes and prevention of LBP remains a major concern. This activity aimed to improve community knowledge regarding the causes and prevention of LBP. The methods included health education sessions, demonstrations of ergonomic postures, and simple stretching exercises, with evaluation conducted using pretest and posttest assessments. The results showed an improvement in participants’ knowledge following the intervention. At the pretest, 53% of participants had a low level of knowledge about LBP. After the intervention, no participants remained in the low-knowledge category, with 60% demonstrating a moderate level of knowledge and the remainder showing good knowledge. It can be concluded that this activity was effective in improving community knowledge regarding LBP and its prevention.